2020
DOI: 10.1088/1361-6587/abab5d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of impurity radiation and helium particle confinement on tokamak–reactor plasma performance

Abstract: In this paper two important matters for assessments the D–T plasma performance of future tokamak–reactors such as ITER and EU–DEMO projects are discussed. The first issue is the heat removal via the radiation of intrinsic and seeded impurities. The second is the helium particle confinement and ash removal. To study these issues, a simple numerical 0.5D-model is proposed. The impurity radiation in the tokamak high–temperature plasma is described by the coronal model. Coronal radiative cooling used rates are bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…On the other hand, the thermal He-4 fraction shows a linear increase in feasibility. These results may indicate that the plasma elongation should be at least 1.83 to fulfill the net electric power output constraint of 400 MW, and greater concentrations of thermal He-4 in the plasma are favorable to achieve the pulselength constraint of 2 h. In fact, it has been shown that greater fusion power is associated with larger elongations [6], and He-4 contributes to increase the energy confinement time when it does not exceed the dilution upper limit [25]. To visualize the combination effects on the feasibility space, the scatterplots of the plasma elongation against the thermal He-4 fraction are displayed on the top right and bottom left figures of Fig.…”
Section: Resultsmentioning
confidence: 95%
“…On the other hand, the thermal He-4 fraction shows a linear increase in feasibility. These results may indicate that the plasma elongation should be at least 1.83 to fulfill the net electric power output constraint of 400 MW, and greater concentrations of thermal He-4 in the plasma are favorable to achieve the pulselength constraint of 2 h. In fact, it has been shown that greater fusion power is associated with larger elongations [6], and He-4 contributes to increase the energy confinement time when it does not exceed the dilution upper limit [25]. To visualize the combination effects on the feasibility space, the scatterplots of the plasma elongation against the thermal He-4 fraction are displayed on the top right and bottom left figures of Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The hybrid scenario, which is an intermediate operation mode, has been investigated in several experimental devices [4][5][6]. On the other hand, significant degradation of core plasma performance has been reported due to radiation losses as a result of accumulation of high-Z impurities such as tungsten (W), which is used for the divertor and vacuum vessel wall material in fusion reactors [7][8][9]. In particular, the impurity accumulation can be accelerated in the ITB region of improved confinement discharges in negative magnetic shear mode and high-β p mode.…”
Section: Introductionmentioning
confidence: 99%
“…In order to withstand the peak heat fluxes during fusion reactor operation, avoid tritium fuel retention and minimize target erosion, next-generation tokamaks like ITER and SPARC are relying on the use of tungsten (W) divertors [1,2]. However, plasma contamination with such a high-Z material can severely restrict the operational space of a reactor [3,4]. Several current devices, like ASDEX Upgrade (AUG) and JET, have transitioned to all-metal walls to study plasma performance in metallic environments in preparation for these future machines [5,6].…”
Section: Introductionmentioning
confidence: 99%